The Effect of Discovery Learning Model with Audio Visual Media on Student Learning Outcomes - Yusmawati Yusmawati; Cecep Anwar Hadi Firdos Santosa; Suroyo Suroyo; Khairul Anwar (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to determine the effect of discovery learning models with audio-visual media on student learning outcomes and to examine differences in learning outcomes between students with high self-confidence compared to students with low self-confidence. The method used in this study is a quasi-experimental involving 5th-grade elementary school students in the Natural Sciences subject. The results showed that the discovery learning model with audio-visual and games had a significant difference in overall science learning outcomes. There is a difference in student science learning outcomes between students with high self-confidence and students with low self-confidence.